1991
DOI: 10.1007/bf00771014
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of redox-associated protons in growth of plant cells

Abstract: The protons excreted by plant cells may arise by two different mechanisms: (1) by the action of the plasma membrane H(+)-ATPase and (2) by plasma membrane redox reactions. The exact proportion from each source is not known, but the plasma membrane H(+)-ATPase is, by far, the major contributor to proton efflux. There is still some questions of whether the redox-associated protons produced by NADH oxidation on the inner side of the plasma membrane traverse the membrane in a 1:1 relationship with electrons genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…salina is very sensitive to osmotic shock. Except of slight hyperosmtic shock, abrupt hyperosmotic shock and hypoosmotic shock greatly decreased the rates of NADH oxidation and Fe(CN) 6 3-reduction (Tab 1), which is in accordance with the phenomenon observed by Crane and Barr under salt stress [3] and Qiu et al under water stress [4]. The electron transport chains of plasmalemma redox system are multiple [11,12 ]: innerside or outerside cis-plasmalemma electron transfer; inward or outward transplasmalemma electron transfer etc.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…salina is very sensitive to osmotic shock. Except of slight hyperosmtic shock, abrupt hyperosmotic shock and hypoosmotic shock greatly decreased the rates of NADH oxidation and Fe(CN) 6 3-reduction (Tab 1), which is in accordance with the phenomenon observed by Crane and Barr under salt stress [3] and Qiu et al under water stress [4]. The electron transport chains of plasmalemma redox system are multiple [11,12 ]: innerside or outerside cis-plasmalemma electron transfer; inward or outward transplasmalemma electron transfer etc.…”
Section: Discussionsupporting
confidence: 83%
“…This process is very important in the reaction and adaptation of plants to various environmental stress, such as pathogen, drought, low temperature, hypoosmotic shock and UV radiation. Barr and Crane [3] found that the redox system in the plasmalemma of carrot cells was very sensitive to salt stress, both NADH oxidation, Fe(CN) 6 3-reduction and H + extrusion were inhibited. Qiu et al [4] also demonstrated that the redox activities in the plasmalemma of wheat root cells were greatly decreased under water stress.…”
Section: Introductionmentioning
confidence: 99%
“…different plant species contain oxidases that generate ROS and regulate vital physiological functions such as seed germination and root hair growth (32,33). We reasoned by analogy that pollen germination is likely to require ROS generated by these oxidases during pollination processes.…”
Section: All Pollens Tested Possessed Intrinsic Nadph Oxidase Activitmentioning
confidence: 99%
“…Other evidence indicates that the effects of boron on membrane function may be associated more directly with proton pumping or changes in a redox system in the plasmalemma. Both the hyperpolarization of the membrane potential (in sunflower roots) and the stimulation of the ferricyanide reduction (in carrot cells) could be related to the activity of NADH oxidase, an enzyme that could provide protons for export (15,16). In 1991, Barr and Crane (17) reported that the activity of plasmalemma NADH oxidase was stimulated by boron.…”
Section: Possible Effects Ofboron On Plant Membrane Functionsmentioning
confidence: 99%